2021
DOI: 10.1111/tbed.14179
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the factors that determine the emergence of anthroponotic cutaneous leishmaniasis due to Leishmania tropica in Morocco: Density and mitochondrial lineage of Phlebotomus sergenti in endemic and free areas of leishmaniasis

Abstract: Anthroponotic cutaneous leishmaniasis (ACL) due to Leishmania tropica is spreading to new areas in Morocco. Exposure to the vector, Phlebotomus sergenti, is the only proven risk factor. Our objective was to compare the densities and genetic characteristics of P. sergenti populations in two nearby localities in Morocco, one in an ACL endemic area (El Borouj) and another in a nonendemic area (Sidi Hajjaj). P. sergenti density was significantly higher in the endemic area than in the nonendemic town (p = 0.032). A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Another study was carried out in the prefecture of Meknes and showed the positive correlation of Leishmania sandfly abundance with temperature ( r = 0.99) and the negative correlation with humidity and precipitation ( r = − 0.87 and r = − 0.72) [ 89 ]. Another study compared the densities and genetic characteristics of Phlebotomus sergenti (kind of Leishmania sandfly) populations in two nearby localities, one in an anthroponotic cutaneous leishmaniasis (ACL, transmissible from humans) endemic area and another in a non-endemic area [ 92 ]. Authors found that P. sergenti density was significantly higher in the endemic area than in the non-endemic town.…”
Section: Resultsmentioning
confidence: 99%
“…Another study was carried out in the prefecture of Meknes and showed the positive correlation of Leishmania sandfly abundance with temperature ( r = 0.99) and the negative correlation with humidity and precipitation ( r = − 0.87 and r = − 0.72) [ 89 ]. Another study compared the densities and genetic characteristics of Phlebotomus sergenti (kind of Leishmania sandfly) populations in two nearby localities, one in an anthroponotic cutaneous leishmaniasis (ACL, transmissible from humans) endemic area and another in a non-endemic area [ 92 ]. Authors found that P. sergenti density was significantly higher in the endemic area than in the non-endemic town.…”
Section: Resultsmentioning
confidence: 99%